Taxonomic study of the genus Microplitis Förster, 1862 (Hymenoptera, Braconidae, Microgastrinae) from Iran - Abdoli, Parisa; Talebi, Ali Asghar; Fernandez-Triana, Jose; Farahani, Samira (European Journal of Taxonomy, 2021)
The genus Microplitis Förster, 1862 (Hymenoptera, Braconidae, Microgastrinae) was studied from northern Iran. Specimens were collected using Malaise traps during 2010–2011. A total of 13 species were collected and identified, of which six species are recorded for the first time from Iran: M. cebes Nixon, 1970, M. docilis Nixon, 1970, M. eremitus Reinhard, 1880, M. kaszabi Papp, 1980, M. pallidipennis Tobias, 1964 and M. varipes (Ruthe, 1860). Two species M. kaszabi and M. pallidipennis are new records for the west Palaearctic region. A new species, Microplitis alborziensis Abdoli & Talebi sp. nov., is described and illustrated. The number of species of Microplitis in Iran is now raised from 17 to 24. A faunistic list, an identification key to all known Iranian species and brief diagnoses and illustrations for all species that have been collected in this study are provided. The validity of the new species is supported by DNA barcoding.